A coordinated x-ray and optical campaign of the nearest massive eclipsing binary, δ orionis Aa. III. Analysis of optical photometric (MOST) and spectroscopic (ground-based) variations - Benvenuto, Omar Gustavo (2015)
We report on both high-precision photometry from the Microvariability and Oscillations of Stars (MOST) space telescope and ground-based spectroscopy of the triple system δ Ori A, consisting of a binary O9.5II+early-B (Aa1 and Aa2) with P = 5.7 days, and a more distant tertiary (O9 IV years). This data was collected in concert with X-ray spectroscopy from the Chandra X-ray Observatory. Thanks to continuous coverage for three weeks, the MOST light curve reveals clear eclipses between Aa1 and Aa2 for the first time in non-phased data. From the spectroscopy, we have a well-constrained radial velocity (RV) curve of Aa1. While we are unable to recover RV variations of the secondary star, we are able to constrain several fundamental parameters of this system and determine an approximate mass of the primary using apsidal motion. We also detected second order modulations at 12 separate frequencies with spacings indicative of tidally influenced oscillations. These spacings have never been seen in a massive binary, making this system one of only a handful of such binaries that show evidence for tidally induced pulsations.